Utopia : Three Plays for a Postdramatic Theatre. - MacDonald, Claire (Playtext series., 2015)
In a room in the middle of nowhere, a man and a woman dream up spectacular worlds: a decaying city, a lush and crumbling garden, a train journey across a drowned landscape. Darkly humorous, absurd and surreal, these are plays for a theatre in which time and space, character and setting are as uncertain as the maps this man and this woman draw. A co-founder of the legendary 1980s performance theatre company Impact Theatre Co-op, Claire MacDonald composed Utopia, a sequence of commissioned playtexts, between 1987 and 2008. This edition brings together both the plays and the story of how the play.